(untitled) (Altre Modernità, 2021)
This article deals with the modes of representation of torture in the science fiction novel by Chilean writer Claudio Jaque El ruido del tiempo (1987), paying special attention to the analysis of the diverse and proliferating modes that, in the framework of a revolt against a totalitarian regime, the rebels develop to resist the torments and succeed in defeating power.